Efficacy and Safety of Cap Assisted vs. Conventional Endoscopic Esophageal Foreign Body Removal - : Systematic Review and Meta-analysis - Renno, Anas (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.